Strategi Bertahan Orang Kuat Lokal (Studi Tentang Perjalanan Hidup Orang Kuat Lokal dalam Figure Abah Encang di Kabupaten Majalengka - , MUTHIARA GUSTHAELA M. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The presence of a local great man in Indonesia can be seen clearly after the collapse of New Order. Few examples of the local great men are Chasan Scohib from Banten, Yasin Daeng Limpo from South Sulawesi, and many else â as well as the presence of Nazzar Hidayat from Majalengka. The phenomenon of a local great man in Majalengka occured during decentralization era. The local great man in Majalengka exists in the form of Godfather. The Godfather is known by his brutal and fierce character to his enemies, but compassionate and generous to his followers. The protective father figure is reflected on Nazar Hidayat, who is renowned as a felon but like an angel for his followers. The presence of a local great man in Majalengka has been steadily occuring since New Order era to present. The strength that makes Nazzar survive to present brings out a question âHow does Nazzar Hidayat maintain his authority as a local great man in Majalengka?â then becomes the problem formulation in this research. Through this problem formulation, the research wants to show how a local great man in Majalengka maintain his authority from his journey, through the journey of his life in the form of biography. The writing of his biography is done to find epiphany that can be traced from his daily life. In this study, the researcher draws explanations of Migdal about the way of a local great man survives when he is able to collaborate with the state, forming political parties, and control resource. This can be illustrated through the triangle of accomodation. The triangle of accomodation can explain authorities of which is owned by Nazzar Hidayat to maintain his position. Nazzar is a strong, harsh, and ruthless man, widely feared by his opponents is a formation of character when he underwent life \"on the street\" for decades.